An inverse relationship between South China Sea summer monsoon intensity and ENSO. Issue 1 (1st January 2021) - Choi, Jae-Won
Abstract: Correlations between the South China Sea summer (June-September) monsoon (SCSSM) and El Niño Southern Oscillation (ENSO) for the past 32 years (1979–2010) were analyzed. As a result, a higher (lower) SST in the Niño-3.4 areas was associated with a weaker (stronger) SCSSM intensity. To examine the cause of this correlation, the differences between the June-September average of 8 El Niño years and the June-September average of 8 La Niña years were analyzed. Differences in the 850 hPa stream flows between the two groups found that anomalous huge cyclones existed in the subtropical Pacific regions of both hemispheres, which reinforced cold and dry anomalous northerlies in the SCS and anomalous westerlies from the Maritime Continent (MC) to the coastal waters of Chile. An analysis of the differences in the 200 hPa stream flows between the two groups found an anomalous pressure system pattern that was opposite to the result of the analysis of the differences in the 850 hPa stream flows between the two groups. Anomalous anticyclones existed in the subtropical Pacific of both hemispheres, which reinforced the anomalous easterlies from the MC to the equatorial central Pacific. When the anomalous atmospheric circulations of the upper and lower layers of the troposphere were also considered, the structure of anomalous atmospheric circulations in which the air current that rose in the equatorial central and eastern Pacific fell down in the MC. This indicates weakening of the Walker Circulation and a typical structure of atmospheric circulations that appears in El Niño years.